Faktor Risiko Keberlanjutan Finansial Berbasis Pemangku Kepentingan Proyek Jalan Tol di Indonesia - Lala Anggraini; Jumiati Bandu; Alif S Mulyati; Amrin Farikhi (Universitas Muhammadiyah Surabaya, 2026)
The financial sustainability of Public-Private Partnership (PPP) toll road projects in Indonesia faces serious challenges due to heavy reliance on conventional debt-based financing, particularly syndicated bank loans that are vulnerable to interest rate fluctuations. This study aims to identify risk factors affecting the financial sustainability of toll road projects and to explore the potential of Islamic financing instruments particularly sukuk as a structural risk mitigation strategy in infrastructure financing. A qualitative approach was adopted using thematic analysis through semi-structured in-depth interviews with two groups of informants: (1) practitioners from toll road operating companies (BUJT) who have direct experience in managing construction and operational risks, and (2) Islamic finance experts with expertise in structuring Sharia-compliant financing instruments. The study identifies four main risk clusters: financing structure risk, construction-phase risk, operational revenue risk, and regulatory risk. The two most critical risks are interest rate fluctuation on syndicated loans and construction cost overruns. Findings reveal that project-based ijarah sukuk offers structural advantages over conventional bonds, particularly in terms of cost of capital certainty (fixed return), asset-backed governance strengthening, and alignment with the long-term cash flow profile of toll road projects. The study underscores the need for financing diversification through the integration of instruments as part of a proactive strategy for managing infrastructure project financial risk.